2020
DOI: 10.47836/pjssh.28.4.32
|View full text |Cite
|
Sign up to set email alerts
|

Fulfilling the Demand for Workplace Communication Skills in the Civil Engineering Industry

Abstract: Human resources today must be nurtured with the skills needed at the workplace in preparation for future challenges. Many engineering graduates nowadays are facing difficulties in adapting themselves to the workplace. They are highly dependent on academic qualifications and underestimate the need for skilled workers who are not only technically proficient but have high competencies of soft skills, especially communication skills. The ability of graduates to communicate effectively can have a significant impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The findings confirm this view, and we find that both skill dimensions of engineering students educated on big data analytics courses have a positive impact on human capital in the employability dimension. This result is consistent with the research of scholars such as Mauro et al (2017), Masduki and Zakaria (2020), and Escolà-Gascón and Gallifa (2022), which indicates that among the three abilities of the hard skills dimension developed by the big data analytics course, the higher the knowledge level, technical skills and analysis skills, the higher the employability of engineering students (Mauro et al, 2017;Escolà-Gascón and Gallifa, 2022). Among the three soft skills cultivated in the course, the cultivation of decisionmaking ability and communication ability enhances students' inherent thinking mode and learning habits, improves their learning ability, and correspondingly enriches students' internship experience and ability to make systematic career planning (Masduki and Zakaria, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The findings confirm this view, and we find that both skill dimensions of engineering students educated on big data analytics courses have a positive impact on human capital in the employability dimension. This result is consistent with the research of scholars such as Mauro et al (2017), Masduki and Zakaria (2020), and Escolà-Gascón and Gallifa (2022), which indicates that among the three abilities of the hard skills dimension developed by the big data analytics course, the higher the knowledge level, technical skills and analysis skills, the higher the employability of engineering students (Mauro et al, 2017;Escolà-Gascón and Gallifa, 2022). Among the three soft skills cultivated in the course, the cultivation of decisionmaking ability and communication ability enhances students' inherent thinking mode and learning habits, improves their learning ability, and correspondingly enriches students' internship experience and ability to make systematic career planning (Masduki and Zakaria, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…From the analysis conducted, the studies were done in various contexts, including maritime (Ahmmed et al, 2020;Alibakhshi & Labbafi, 2021), engineering (Adnan, 2019;Baklazhenko, 2018;Gözüyeşil, 2014;Masduki & Zakaria, 2020;Panyawong-Ngam et al, 2015;Spence & Liu, 2013), medicine (Arumugam & Kaur, 2011), mechatronics (Ranasuriya & Herath, 2020), pest control (Hee & Zainal, 2018), human resource (Moslehifar & Ibrahim, 2012), information technology (Fareen, 2018), military and/or aviation (Alshabeb et al, 2017;Sari & Sari, 2020), architecture (Palea et al, 2012) and a combination of multiple industries (Al-Buainain, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Panyawong-Ngam et al (2015), on the other hand, considered listening as the most important skill, followed by writing and reading. One study identified speaking, writing, interpersonal and visual communication as the most important skills for the workplace in the context of civil engineering (Masduki & Zakaria, 2020).…”
Section: Most Important Communication Skillsmentioning
confidence: 99%
See 2 more Smart Citations